The Effect of the Timing and Direction of Capital Gain Tax Changes on Investment in Risky Assets - Falsetta, Diana; Rupert, Timothy J.; Wright, Arnold M. (The Accounting Review, 2013)
ABSTRACT This study examines the effect of timing (gradual versus immediate) and direction (tax increase or decrease) of a tax change on taxpayer behavior. Specifically, we focus on capital gain tax changes and preferences for investment in riskier assets. We run an experiment with 117 participants who allocate investment dollars between two funds of differing risk. Drawing on mental accounting and hedonic editing (Thaler 1985; Thaler and Johnson 1990), we posit that a tax decrease (a “gain”) implemented gradually over several years will result in a greater increase in risky investment once the decrease is fully implemented than when the tax change is implemented all at once. In contrast, once a tax increase (a “loss”) is fully implemented, a smaller decrease in risky investment will result when the change occurs all at once rather than gradually. Our findings support these expectations, suggesting that the manner of implementing a tax law change may impact decisions. Data Availability: Contact the authors.